2018
DOI: 10.1111/jgs.15617
|View full text |Cite
|
Sign up to set email alerts
|

Senior PharmAssist: Less Hospital Use with Enrollment in an Innovative Community‐Based Program

Abstract: Objectives To evaluate changes in acute health services use of Senior PharmAssist participants. Design Retrospective analysis. Setting Community‐based, nonprofit program in Durham County, North Carolina. Participants Adults aged 60 and older with income of 200% of the federal poverty level or less who enrolled in the Senior PharmAssist program (N = 191) between August 1, 2011, and March 15, 2017. Intervention Medication therapy management (MTM), customized community referrals, Medicare insurance counseling, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“… 5 Unlike previous studies, no significant differences were found regarding hospital visits, ED visits, or combined hospital and ED visits. 5 , 6 , 7 Compared to other studies, this study is unique due to collaboration between clinical pharmacists and MAP coordinator to improve outcomes and prevent disease progression while ensuring patients are successfully accessing previously unaffordable medications. 6 , 7 Utilization of the MAP coordinator increases efficiency of the MAP application process as well as reduces the burden and difficulty of completing the initial application, refill requests, and application renewals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 Unlike previous studies, no significant differences were found regarding hospital visits, ED visits, or combined hospital and ED visits. 5 , 6 , 7 Compared to other studies, this study is unique due to collaboration between clinical pharmacists and MAP coordinator to improve outcomes and prevent disease progression while ensuring patients are successfully accessing previously unaffordable medications. 6 , 7 Utilization of the MAP coordinator increases efficiency of the MAP application process as well as reduces the burden and difficulty of completing the initial application, refill requests, and application renewals.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 , 7 Compared to other studies, this study is unique due to collaboration between clinical pharmacists and MAP coordinator to improve outcomes and prevent disease progression while ensuring patients are successfully accessing previously unaffordable medications. 6 , 7 Utilization of the MAP coordinator increases efficiency of the MAP application process as well as reduces the burden and difficulty of completing the initial application, refill requests, and application renewals. A MAP coordinator is a vital component to our successful MAP process for indigent and underserved patient populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2015 to 2020, the Duke Geriatric Workforce Enhancement Program—a grant‐funded workforce development program—partnered with Senior PharmAssist, a community‐based organization focused on the medication and insurance needs of older adults in Durham, North Carolina 24,25 . During this time, it was determined that medication reconciliation for community‐dwelling under‐resourced older adults was a pressing concern and the Durham Medication Reconciliation Initiative was formed.…”
Section: Methodsmentioning
confidence: 99%
“…From 2015 to 2020, the Duke Geriatric Workforce Enhancement Program-a grant-funded workforce development program-partnered with Senior PharmAssist, a community-based organization focused on the medication and insurance needs of older adults in Durham, North Carolina. 24,25 During this time, it was determined that medication reconciliation for community-dwelling underresourced older adults was a pressing concern and the Durham Medication Reconciliation Initiative was formed. The Initiative's leadership team included representatives from Senior PharmAssist, several academically-affiliated providers, and a university-based community-engaged research group, the Community Engaged Research Initiative (CERI) within the Duke Medical Center Clinical and Translational Science Institute (CTSI).…”
Section: Overviewmentioning
confidence: 99%